The comparison of post-proximal gastrectomy digestive tract reconstruction methods - Yang Xia; Nengquan Sheng; Zhigang Wang; Qingchao Zhu (BMC Surgery)
Abstract Objective Proximal gastrectomy (PG) is commonly used to remove proximal gastric cancer leading to gastroesophageal reflux and requires digestive tract reconstruction. This study is to compare the performance of esophagogastrostomy (EG), jejunal interposition (JI), and double tract reconstruction (DTR) on post-PG reconstruction effectiveness. Methods A retrospective study was conducted using the clinical data of 94 PG patients who underwent digestive tract reconstruction by EG (37 patients), JI (29 patients) or DTR (28 patients). The safety of the reconstruction procedure and the incidence of surgical complications were evaluated using the Reflux Symptom Index (RSI), Gastroesophageal Reflux Disease Questionnaire (GERD-Q) scale score, gastroscopy, barium meal examination of digestive tract, and 24-h pH monitoring. Results The DTR group showed significantly lower GERD-Q scores (p < 0.05) and RSI scores (p < 0.05) compared to the EG and JI groups. This indicates that DTR is more effective in preventing reflux esophagitis. The pre- and post-surgical GERD-Q scores assessed by esophageal 24-h pH acidity measurements and Los Angeles Grading were reduced in all patient groups, with the DTR group showing better results than the other two (p < 0.05). The results of the EORTC QLQ-STO22 questionnaire indicated that the DTR group had a higher overall health status score than the other two groups (p < 0.001). Conclusion EG had a short surgical duration and less bleeding. JI reduced the prevalence of reflux esophagitis. DTR presented improved prevention of reflux esophagitis and enhanced quality of life.